First Molecular Detection of Aichivirus in Pediatric Patients with Acute Gastroenteritis in Iran - Taghinejad, Mohammad; Ghaderi, Mostafa; Mousavi‑Nasab, Seyed Dawood (Novelty in Biomedicine, 2020)
Background: Aichivirus as a new member of Picornaviridae family was detected and isolated in Japan. Aichivirus species, which belongs to genus Kobuvirus, include of three genotypes A, B and C. Based on previous reports to detect aichiviruses in stool samples as well as environmental samples such as river waters and sewage waters, it has been demonstrated that Aichivirus infect humans by fecal-oral routs. In order to establish an examination for the prevalence of Aichivirus among pediatric patients involved to acute gastroenteritis, we conducted a RT-qPCR assay for detection and quantification of Aichivirus in collected stool samples. Materials and Methods: In this study, a total of 160 stool samples from September 2018 to May 2019 were collected from presenting pediatric patients with acute gastroenteritis in Karaj hospital, Iran. After viral RNA extraction, the RT-PCR was performed to amplify the 3CD junction region of Aichivirus. Results: Out of the 160 samples tested, the Aichivirus genomic RNA was detected in 13/160 (8.1%) of stool samples. The maximum viral prevalence rate was related to December (30.7%). The co-infection of Aichivirus with Salivirus and Saffold virus also assessed, among which high double or triple mixed-infections were determined. Conclusion: This is the first documentation of Aichivirus detection in stool samples that demonstrates Aichivirus has been circulating among Iranian pediatric patients. Our results indicate that Aichivirus in association with Salivirus and Saffold virus may be considered as a causative agent of acute gastroenteritis.